Glecaprevir and Maraviroc are high-affinity inhibitors of SARS-CoV-2 main protease: possible implication in COVID-19 therapy - Shamsi, Anas (Biosci Rep, 2020)
Due to the lack of efficient therapeutic options and clinical trial limitations, the FDA-approved drugs can be a good choice to handle Coronavirus disease (COVID-19). Many reports have enough evidence for the use of FDA-approved drugs which have inhibitory potential against target proteins of Severe Acute Respiratory Syndrome Coronavirus 2 (SARS-CoV-2). Here, we utilized a structure-based drug design approach to find possible drug candidates from the existing pool of FDA-approved drugs and checked their effectiveness against the SARS-CoV-2. We performed virtual screening of the FDA-approved drugs against the main protease (M(pro)) of SARS-CoV-2, an essential enzyme, and a potential drug target. Using well-defined computational methods, we identified Glecaprevir and Maraviroc (MVC) as the best inhibitors of SARS-CoV-2 M(pro). Both drugs bind to the substrate-binding pocket of SARS-CoV-2 M(pro) and form a significant number of non-covalent interactions. Glecaprevir and MVC bind to the conserved residues of substrate-binding pocket of SARS-CoV-2 M(pro). This work provides sufficient evidence for the use of Glecaprevir and MVC for the therapeutic management of COVID-19 after experimental validation and clinical manifestations.